Epidemiological and clinical characteristics of patients with monkeypox in the GeoSentinel Network: a cross-sectional study. Issue 2 (February 2023) - Angelo, Kristina M; Smith, Teresa; Camprubí-Ferrer, Daniel; Balerdi-Sarasola, Leire; Díaz Menéndez, Marta; Servera-Negre, Guillermo; Barkati, Sapha; Duvignaud, Alexandre; Huber, Kristina L B; Chakravarti, Arpita; Bottieau, Emmanuel; Greenaway, Christina; et al.
Summary: Background: The early epidemiology of the 2022 monkeypox epidemic in non-endemic countries differs substantially from the epidemiology previously reported from endemic countries. We aimed to describe the epidemiological and clinical characteristics among individuals with confirmed cases of monkeypox infection. Methods: We descriptively analysed data for patients with confirmed monkeypox who were included in the GeoSentinel global clinical-care-based surveillance system between May 1 and July 1 2022, across 71 clinical sites in 29 countries. Data collected included demographics, travel history including mass gathering attendance, smallpox vaccination history, social history, sexual history, monkeypox exposure history, medical history, clinical presentation, physical examination, testing results, treatment, and outcomes. We did descriptive analyses of epidemiology and subanalyses of patients with and without HIV, patients with CD4 counts of less than 500 cells per mm 3 or 500 cells per mm 3 and higher, patients with one sexual partner or ten or more sexual partners, and patients with or without a previous smallpox vaccination. Findings: 226 cases were reported at 18 sites in 15 countries. Of 211 men for whom data were available, 208 (99%) were gay, bisexual, or men who have sex with men (MSM) with a median age of 37 years (range 18–68; IQR 32–43). Of 209 patients for whom HIV status was known, 92 (44%) men had HIV infection with a median CD4 count of 713 cells per mm 3 (range 36–1659; IQR 500–885). Of 219 patients for whom data were available, 216 (99%) reported sexual or close intimate contact in the 21 days before symptom onset; MSM reported a median of three partners (IQR 1–8). Of 195 patients for whom data were available, 78 (40%) reported close contact with someone who had confirmed monkeypox. Overall, 30 (13%) of 226 patients were admitted to hospital; 16 (53%) of whom had severe illness, defined as hospital admission for clinical care rather than infection control. No deaths were reported. Compared with patients without HIV, patients with HIV were more likely to have diarrhoea (p=0·002), perianal rash or lesions (p=0·03), and a higher rash burden (median rash burden score 9 [IQR 6–21] for patients with HIV vs median rash burden score 6 [IQR 3–14] for patients without HIV; p<0·0001), but no differences were identified in the proportion of men who had severe illness by HIV status. Interpretation: Clinical manifestations of monkeypox infection differed by HIV status. Recommendations should be expanded to include pre-exposure monkeypox vaccination of groups at high risk of infection who plan to engage in sexual or close intimate contact. Funding: US Centers for Disease Control and Prevention, International Society of Travel Medicine.